A Comparative Study of Apology Strategies produced by Indonesian and Australian Bridge Players - Fanny Misfa Jessy; Thomas Joko Priyo Sembodo (Universitas Gadjah Mada, 2019)
This study aims to identify, classify, and compare the apology strategies used by Indonesian and Australian bridge players. The data were gathered from 10 Indonesian bridge players and 10 Australian bridge players through a Discourse Completion Task (DCT) questionnaire. There are 173 apology strategies found among Indonesian bridge players and 146 apology strategies among Australian bridge players. The data are classified by the categorization adapted from previous research such as Cohen and Olshtain (1981), Blum-Kulka and Olshtain (1984) and Shahrokhi and Jan (2012). The result of the study shows some similarities and differences in terms of frequency of apology strategies used by Indonesian and Australian bridge players. The findings of this study describe the speech acts of apology between two groups of people with different cultural backgrounds.